Characterization of Oesophagostomum asperum and O. columbianum by internal transcribed spacers of nuclear ribosomal DNA. Issue 1 (March 2014) - Zhao, G.H.; Hu, B.; Song, J.K.; Jia, Y.Q.; Li, H.M.; Wang, C.R.; Lin, Q.; Xu, Q.X.; Yu, S.K.; Deng, Y.
Abstract In the present study, the internal transcribed spacers (ITS) of ribosomal DNA (rDNA) of Oesophagostomum asperum and O. columbianum were amplified and sequenced. The ITS-1, 5.8S and ITS-2 rDNA sequences of O. asperum were 374 bp, 153 bp and 259 bp in length, respectively, and the corresponding sequences of O. columbianum were 259, 153 and 218 bp in length, respectively. Sequence differences in the ITS-1 and ITS-2 rDNA between the two Oesophagostomum species were 9.5–10.2% and 12.7–13.9%, respectively. Sequence differences in the ITS-1 and ITS-2 rDNA among members of the genus Oesophagostomum were 2.5–11.6% and 6.8–22.3%, respectively. Based on genetic markers in the ITS rDNA, an effective polymerase chain reaction (PCR) approach was developed to differentiate O. columbianum from O. asperum with a sensitivity of 0.2 ng/μl DNA. Since accurate characterization of parasites at different taxonomic levels is essential for population genetic studies and control of parasitosis, the present findings have important implications for studying epidemiology, taxonomy and population biology, as well as for the control of oesophagostomiasis.